UM RELATO AUTOBIOGRÁFICO DE UM SURDO SOB O VIÉS DAS POLÍTICAS EDUCACIONAIS INCLUSIVAS - LENARTOVICZ, LUCAS EMANOEL (2023)
It is known the importance of Sign Language in the formation of the deaf subject for social inclusion. In a majority hearing society in which oral language predominates, the deaf person does not actually get to participate in the process of inclusion in society and this ends up portraying the linguistic development of the deaf, preventing him from being understood. Through the conception that human development takes place in interaction with the social, historical and cultural environment, we highlight the need for this environment to be organized, as this development does not occur naturally and spontaneously, but intentionally. In this context, Proposing an inclusive educational policy is based on the thought of accepting and recognizing that education encompasses diversity, that is, each subject has its particularities, and that this must guarantee access, permanence and successful completion for all. As well as the philosophy that a quality education is one that respects and performs the service according to the educational needs of each one. This dissertation is an autobiographical research, based on an autobiographical account of a deaf person under the bias of inclusive educational policies. Therefore, the general objective of the dissertation was to discuss the life story of a deaf person, based on the autobiographical account relating to the influences of inclusive educational policies. The specific objectives are outlined as follows: a) to understand the epistemological perspectives of autobiographical research, as well as the concepts about the theoretical-methodological foundation related to the theme. b) understand the concepts of terms such as identity, culture, and the historicity of inclusive educational policies enacted by the Brazilian legal system; c) verify how inclusive educational policies influenced the dimensions of a deaf subject's life, through the analysis of my identity construction process as a deaf subject. To respond to these objectives, the methodological path of the research is the autobiographical method, since this methodology presents some peculiar characteristics that allowed me the freedom of thoughts and ideas, factors that contributed to the development of critical reflections based on the narrative. Throughout the investigation, I dismantled and reconstructed parts of my life story. In addition, I reported how my training was, which led me to think and rethink my development. It was necessary to rethink the way in which the role of sign language and natural language, respectively, are understood and a new analysis of my subjectivity and my condition of being deaf is also necessary. This study, which is concerned with my life story, helps to prove the need for teacher training at the moment, in accordance with decree 5626/05. (BRASIL, 2005). I believe that I contributed to a set of reflections and numbers that demonstrate that the deaf individual, even if he has to face many problems, has the capacity to develop his autonomies, acquire knowledge and have a life project that is concerned with changes and believes that are possible.